Neutrophil-to-lymphocyte ratio and CRP-to-albumin ratio in the prediction of catheter-related bloodstream infection among maintenance hemodialysis patients: a synergistical optimization algorithm - Zhao, ZhiPeng; Yuan, Shuang; Zhang, XiuLi; Li, Hang; Liu, XiaoYing; Zhang, LiHong; Wang, Tao (Frontiers in Medicine, 2025)
BackgroundAn improved prediction method concurrently using neutrophil-to-lymphocyte ratio (NLR) and CRP-to-albumin ratio (CAR) was herein developed for catheter-related bloodstream infection (CRBSI), which is a potentially life-threatening complication in maintenance hemodialysis (MHD) patients.MethodsIn a multicenter retrospective cohort study, MHD patients using central venous catheter in the past 3 years were divided into infected and uninfected groups by the events of CRBSI. Inter-group difference was examined by either t-test or chi-square test. Positive findings were further stepwisely explored for independent effect, diagnostic efficacy and synergistic action on the CRBSI by binary logistic regression analysis, receiver operating characteristic (ROC) curve and multiple dimensionality reduction (MDR) method, respectively. Findings up to the ROC curve were separately validated in a second cohort, which was then incorporated for the testing of MDR method.ResultsEligible patients with and without CRBSI were 140 and 249, respectively. Hemoglobin (Hb), NLR, CAR, cholesterol, ferritin, and catheter type showed major inter-group differences and their independent effect on the CRBSI was confirmed by the regression analysis. These findings were literally validated in the second cohort. The ROC curve subsequently yielded a cutoff value of 6.115 for the NLR and 0.345 for the CAR. Accordingly, patients simultaneously manifesting higher NLR and CAR had the utmost risk for CRBSI as confirmed by the MDR method and vice versa.ConclusionAs such, NLR and CAR are inexpensive, replicable and easily measurable hematological indices for the prediction of future onset of CRBSI in asymptomatic patients, with better applicability and accuracy upon concurrent use.